ANALISIS KEUNTUNGAN JAGUNG MANIS DI SUBAK MAMBAL KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Namput, Verena Merlyn; Tamba, I Made; Budiasa, Made (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2020)
This study entitled Analysis of the Advantages of sweet corn in Subak Mambal, Abiansemal District, Badung Regency. Which aims to: 1) Know the benefits of sweet corn in Subak Mambal, Abiansemal District, Badung Regency. 2) To find out the marketing channel of sweet corn in Subak Mambal, Abiansemal District, Badung Regency. Population was determined by purposive sampling with a number of 150 farmers. Samples were determined using a random sampling method (random). The results of the study showed that the average profit gained by farmers sweet corn in Subak Mambal Rp. 5.606.645/growing season, and found the first marketing channel, namely Farmer-Trader Emperator-Consumer. and the second marketing channel, namely Farmer-Trader-Trader-RetailerConsumer. The first margin received was Rp. 2.570 and on the second marketing channel the margin received was Rp. 3.091.